Temporal trends in physical violence, gender differences and spatial vulnerability of the location of victim's residences. (June 2018) - Cavalcante, Gigliana Maria Sobral; de Macedo Bernardino, Ítalo; da Nóbrega, Lorena Marques; Ferreira, Raquel Conceição; Ferreira e Ferreira, Efigênia; d'Avila, Sérgio
Highlights: The occurrence of physical violence against men and women was high. Spatial-temporal analysis can generate valuable information to combat violence and injuries. Violence rates showed temporal trends according to gender, age group, and place of residence. Temporal analysis revealed a growing trend of violence against women and domestic violence. Violence victims may benefit from preventive and informative public policy campaign. Abstract: The aim of study was to describe trends in physical violence among Brazilian victims and investigate spatial vulnerability of the location of victim's residences. This study performed an ecological-level longitudinal analysis, examining violence rates over 4 years. Cases of 4795 victims of physical aggression attended at a Center of Legal Medicine were investigated. Trend analysis was used to evaluate the data, with the creation of polynomial regression models ( p  < 0.05). Violence rates showed significant temporal variations according to sociodemographic characteristics of victims ( p  < 0.05) and the circumstances of aggressions ( p  < 0.05). Moreover, there was a significant increase in violence rate in the North ( R 2  = 16.1%; p  = 0.019) and South ( R 2  = 18.4%; p  = 0.010), whereas the rural zone ( R 2  = 10.1%; p  = 0.028) presented a decrease. The findings highlight the need for protection policies that address spatial-temporal aspects.